Immune deficiency vs. immune excess in inflammatory bowel diseases-STAT3 as a rheo-STAT of intestinal homeostasis - Leppkes, Moritz; Neurath, Markus; Herrmann, Martin; Becker, Christoph (Journal of Leukocyte Biology, 2016)
Genome-wide association studies have provided many genetic alterations, conferring susceptibility to multifactorial polygenic diseases, such as inflammatory bowel diseases. Yet, how specific genetic alterations functionally affect intestinal inflammation often remains elusive. It is noteworthy that a large overlap of genes involved in immune deficiencies with those conferring inflammatory bowel disease risk has been noted. This has provided new arguments for the debate on whether inflammatory bowel disease arises from either an excess or a deficiency in the immune system. In this review, we highlight the functional effect of an inflammatory bowel disease-risk allele, which cannot be deduced from genome-wide association studies data alone. As exemplified by the transcription factor signal transducer and activator of transcription 3 (STAT3), we show that a single gene can have a plethora of effects in various cell types of the gut. These effects may individually contribute to the restoration of intestinal homeostasis on the one hand or pave the way for excessive immunopathology on the other, as an inflammatory "rheo-STAT".
EVALuna2:1967